Perioperative quality assessment of varicose vein surgery: Commission for quality assessment of the German Society for Vascular Surgery - Noppeney, Thomas; Böckler, Dittmar (Langenbeck's archives of surgery, 2016)
PurposeAn estimated 350,000 varicose vein (VV) surgical procedures are performed in Germany each year, with annual treatment costs amounting to about 800 million Euro. To evaluate the outcome quality of this treatment, we examined the intraoperative and postoperative complication rates on record in the VV surgery quality assessment (QA) registry of the German Society for Vascular Surgery (GSVS).MethodsData on 89,647 patients (27,463 men, 62,184 women; average age 52.8 years, range 15-96 years) collected in the GSVS varicose surgery QA registry between 2001 and 2009 were analyzed. In these patients, 95,214 surgical procedures were performed on 105,296 limbs. Complication rates were correlated with the type of VV surgical procedure, with whether surgery was performed on an inpatient or outpatient basis, and with the CEAP classification (C stage) and American Society of Anaesthesiologists’ (ASA) stage at the time of surgery. Statistical analyses were performed using a chi-square test, a Cochrane-Armitage test, and an odds ratio calculation.ResultsIntraoperative and postoperative complication was low (0.18 and 0.43 %, respectively), being the lowest for radiofrequency ablation (0.25 %) but not differing significantly from those for endovenous laser therapy and high ligation and stripping. General complications occurred in 0.67 % of outpatients and in 0.25 % of inpatients, a highly significant statistical difference (p < 0.0001, chi-square test). With regard to C stage, the higher the stage, the higher the local complication rate. A clear correlation was also found between preoperative ASA stage and postoperative complication rates: for ASA stages I and II, the complication rates were 0.2 and 0.5 %, respectively, increasing for ASA stage III to 1.2 % and for ASA IV to 2.2 %. The differences between the ASA classes were highly statistically significant (p < 0.0001, Cochrane-Armitage test)ConclusionsOutcome quality as reflected in the intraoperative and postoperative complication rates was very good for all patients undergoing inpatient or outpatient VV surgery. Data from the GSVS QA registry shows that VV surgery is performed with very good perioperative results in specialized centers in Germany.
Gesehen am 17.09.2019